PENDAMPINGAN BELAJAR MEMBENTUK KARAKTER ANAK YANG TERDAMPAK PANDEMI COVID-19 MELALUI KEGIATAN INTERAKSI ALAM DAN SOSIAL DI DUSUN KRAJAN DESA KEDUNGGEBANG KECAMATAN TEGALIMO KABUPATEN BANYUWANGI - Ansari Ansari; Siti Maulida Ulva (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2021)
Aqidah Ahlus Sunnah Wal Jama'ah (Aswaja) is the largest aqidah followed by Muslims all over the world. This Aqidah Aswaja contains elements of Islamic aqidah that are relevant and accepted by both naqli and aqli arguments. Moreover, Aswaja's aqidah principles are in accordance with the teachings of Islam which is Rahmatal lil 'Alamiin, which is tawasut or moderate in nature, not extreme right or extreme left.